2021
DOI: 10.1182/blood-2021-147667
|View full text |Cite
|
Sign up to set email alerts
|

High Effectiveness and Safety of Anti-CD7 CAR T-Cell Therapy in Treating Relapsed or Refractory (R/R) T-Cell Acute Lymphoblastic Leukemia (T-ALL)

Abstract: Background Compared with the substantial efficacy of chimeric antigen receptor T-cell (CAR-T) therapy that has achieved in B-ALL, whether CAR-T therapy is effective and safe for patients with T-ALL is still being explored in early stage clinical trials. Here, we present outcomes from our phase 1 clinical trial of CD7-targeting CAR-T (CD7CAR) cells therapy for R/R T-ALL (NCT04572308). Methods Peripheral blood (PB) mononuclear cells were obtained by leukapheresis. T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…conducted a phase I clinical trial of CD7 CAR-T cell therapy for 14 R/R T-ALL. The data showed that 13/14 (92.9%) patients achieved MRD negative CR at day 28 post-infusion and all patients experienced mild CRS (grade<2) ( 84 ). For T-ALL patients, there may be not enough normal T cells for CAR-T cells preparation, Pan et al.…”
Section: Car-t Therapy For Non-b-cell Acute Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…conducted a phase I clinical trial of CD7 CAR-T cell therapy for 14 R/R T-ALL. The data showed that 13/14 (92.9%) patients achieved MRD negative CR at day 28 post-infusion and all patients experienced mild CRS (grade<2) ( 84 ). For T-ALL patients, there may be not enough normal T cells for CAR-T cells preparation, Pan et al.…”
Section: Car-t Therapy For Non-b-cell Acute Leukemiamentioning
confidence: 99%
“…(84). For T-ALL patients, there may be not enough normal T cells for CAR-T cells preparation, Pan et al used donor-derived CD7 CAR-T cells to explore the efficacy and safety in R/R T-ALL, 18/20 patients achieved CR with 7 patients proceeding to HSCT and with a manageable safety profile (67).…”
mentioning
confidence: 99%
“…CRS occurred in 13 patients but was mild in most patients. 51 In addition, in a study comparing anti-CD7 CAR-T-cells with anti-CD19 CAR-T-cells, the investigators found that the cells targeting CD7 proliferated quickly after infusion, and the duration was longer than that of cells targeting CD19. The anti-CD7 CAR-T-cells did not increase the incidence of adverse event compared with anti-CD19 CAR-T-cells.…”
Section: Promising Target Antigens and Solutions To The Challengesmentioning
confidence: 99%
“…Only one patient experienced grade 3 CRS, whereas others experienced grade 1 or 2 CRS. CD7 CAR-T cells persisted in the peripheral blood for a median of 52.5 days at the last evaluation [23].…”
Section: Cd7mentioning
confidence: 99%